2004
DOI: 10.1094/pdis.2004.88.9.1049c
|View full text |Cite
|
Sign up to set email alerts
|

Iris yellow spot virus on Onion in New Mexico

Abstract: Onions are an important crop for New Mexico with 7,700 acres (3,116 ha) harvested in the state in 2003 (3). In 2002, onions of several cultivars were first noticed with diamond-shaped chlorotic or bleached lesions on seed stalks or leaves, typical of those reported for Iris yellow spot virus (IYSV). A more widespread survey of breeding stocks and commercial onion fields revealed similar symptoms on thrips-infested onions in Dona Ana and Rio Arriba counties. Incidence of disease symptoms ranged from <0.5 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…A 'scape blight' of onion first reported in the USA in 1993 (Hall et al, 1993) is also now known to be caused by IYSV (Mohan and Moyer, 2002;Schwartz et al, 2002;du Toit et al, 2003;Creamer et al, 2004;Gent et al, 2004). IYSV has also been detected in onion in Slovenia (Mavric and Ravnikar, 2001), Australia (Coutts et al, 2003) and Japan .…”
Section: Iris Yellow Spot Virus (Iysv)mentioning
confidence: 99%
“…A 'scape blight' of onion first reported in the USA in 1993 (Hall et al, 1993) is also now known to be caused by IYSV (Mohan and Moyer, 2002;Schwartz et al, 2002;du Toit et al, 2003;Creamer et al, 2004;Gent et al, 2004). IYSV has also been detected in onion in Slovenia (Mavric and Ravnikar, 2001), Australia (Coutts et al, 2003) and Japan .…”
Section: Iris Yellow Spot Virus (Iysv)mentioning
confidence: 99%
“…Since 2001, IYSV has been confirmed in all onion-producing states in the western United States, including Arizona, California, Colorado, Idaho, New Mexico, Nevada, Oregon, Utah, and Washington (Creamer et al, 2004;Crowe and Pappu, 2005;du Toit et al, 2004a;Hall et al, 1993;Pappu and Matheron, 2008;Poole et al, 2007;Schwartz et al, 2002) as well as in Georgia (Mullis et al, 2004), Texas (Miller et al, 2006), and New York (Hoepting et al, 2007). An IYSV epidemic in Colorado during 2003 is estimated to have cost growers $2.5 to $5.0 million in farm receipts alone (Schwartz and Gent, unpublished data).…”
mentioning
confidence: 99%
“…IYSV incidence ranged from 58% to 97% among different cultivars. Creamer et al (2004) reported differences in the IYSV incidence of three onion cultivars in growth chamber tests. The objectives of this study were to screen onion germplasm for IYSV tolerance/resistance in terms of disease severity and incidence to determine the correlation between severity ratings and a measure of virus titer in the plant and to determine the relationship of plant sampling for rating selection with mean plot severity.…”
mentioning
confidence: 99%
“…Since 2000, IYSV has been conÞrmed in most onion production areas in the United States (Hall et al 1993, Schwartz et al 2002, Creamer et al 2004, du Toit et al 2004a, Mullis et al 2004, Crowe and Pappu 2005, Miller et al 2006, Pappu and Matheron 2008 and provinces in Canada . In New York, IYSV was Þrst detected in 2006 .…”
mentioning
confidence: 99%